Instrument Development Chapter of Learning Game Football Kick The Ball for Elementary School Grade Five - Sholikhin, Mochamad Nur; Supriyadi, Supriyadi; Soegiyanto, Soegiyanto (Journal of Research and Educational Research Evaluation, 2020)
Authentic assessment at school has generally been carried out, but has not been supported by a tested assessment instrument. The purpose of this study was to produce a valid, reliable, and practical assessment instrument in learning soccer kicking material. The research method used is research and development involving 3 expert assessments, namely, Information Technology Experts, and Sport and health physical education teachers. The expert validation instrument has 4 categories, namely invalid, less valid, valid, very valid. For data analysis, the validity level used the Aiken's V formula, while knowing the reliability level of the instrument used the Cronbach alpha formula assisted by SPSS 16.0. The results of the content validation analysis of all items were valued above 0.3, which means that all aspects assessed by the expert were valid. The reliability test of the assessment instrument using Cronbach's alpha was obtained a value of 0.747. The practicality test of the assessment instrument in the form of a website has a value of 85%. It can be concluded that the instrument application has a very high level of practicality. This study serves to increase the reference data of researchers and of course it can be used by teachers in conducting assessments.